Leveraging the benefits of integrating and interacting electric vehicles and distributed energy resources - Martin Heinrich Paschmann (Institute of Energy Economics at the University of Cologne (EWI), 2017)
In this paper, benefits resulting from the interaction of electric vehicles and photovoltaic generation units are analyzed. In doing so, a bottom-up approach is developed to simulate the driving and charging behavior of electric vehicles. An economic analysis is then performed to determine key findings for households with photovoltaic systems and electric vehicles: First, smart electric vehicle charging concepts may allow households to achieve higher cost-saving potentials by increasing their share of self-consumption by 59% compared to the case of uncontrolled charging. Second, adopting more of a system-oriented perspective, smart electric vehicle charging concepts could react to times of peak load and thereby reduce the average peak-load increase due to electric vehicles to 27%. According to these findings, it may be beneficial for policy makers to encourage peak-load minimizing charging behavior by introducing, e.g., load-sensitive tariff schemes. Technical challenges arising from the peak-load impact of electric vehicles may be regarded as being a coordination problem. Finally, the analysis shows that the potential of electric vehicles to counteract extremes of reverse power flows due to high photovoltaic electricity generation is limited.
Keywords: C15; C61; C63; D14; H20; R20; 330; electromobility; distributed energy resources; energy storage; electric vehicle charging; sector coupling; energy self-sufficiency